Welcome to Scribd, the world's digital library. Read, publish, and share books and documents. See more
Standard view
Full view
of .
0 of .
Results for:
P. 1
Engineer

# Engineer

Ratings: (0)|Views: 0 |Likes:

### Availability:

See more
See less

12/13/2012

pdf

text

original

State the vertex and focus of the parabola having the equation
(
y

–
3)
2
= 8(
x

–
5)
.

Comparing this equation with the conics form, and remembering that the
h
always goes with the
x
and the
always goes with the
y
, I can see that the center is at
(
h
,
) = (5, 3)
. The coefficient of the
unsquared
part is
4
p
; in this case, that gives me
4
p
= 8
, so
p
= 2
. Since the
y
part is squaredand
p
is positive, then this is a sideways parabola that opens to the right. The focus is inside theparabola, so it has to be two units to the right of the vertex:

vertex:
(5, 3)
; focus:
(7, 3)

State the vertex and directrix of the parabola having the equation
(
x
+ 3)
2
=
–
20(
y

–
1)
.

The temptation is to say that the vertex is at
(3, 1)
, but that would be wrong. The conics form of the equation has
subtraction
inside the parentheses, so the
(
x
+ 3)
2
is really
(
x

–
(
–
3))
2
, and thevertex is at
(
–
3, 1)
. The coefficient of the
unsquared
part is
–
20
, and this is also the value of
4
p
,so
p
=
–
5
. Since the
x
part is squared and
p
is negative, then this is a regular parabola thatopens downward. This means that the directrix, being on the outside of the parabola, is five unitsabove the vertex.

vertex:
(
–
3, 1)
; directrix:
y
= 6
Find the equation of the ellipse which has a minor axis of length 8 and a vertex at (0,-5).AnswerWe conclude that
a
=5
and
b
=4
. So the equation of the ellipse is:
x
2
16+
y
2
25=1

Sketch the ellipse with equation
(
x
−1)
2
25+(
y
+2)
2
9=1
AnswerWe first observe that the centre of the ellipse will be at
(1,−2)
. The major axis will have length
10
(since
a
=5
) and the minor axis will be length
6
(since
b
= 3).So the sketch is:e solve the 2 equations simultaneously by substituting the expression
y
=
x
−1
into the expression
x
2
+
y
2
x
−3
y
=0
[See some background to this at: Algebraic Solution of Systems of Equations.] We have:
x
2
+(
x
−1)
2
x
−3(
x
−1)=0

x
2
+
x
2
−2
x
+1−
x
−3
x
+3=0